(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The teacher must constantly search and work for the student to consciously master the books and book-loving topics in the Grade 1Reading textbook. The role of illustration in the presentation of books and book-loving topics is also evaluated separately.